2010
DOI: 10.3109/13668251003694598
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index as an indicator of adiposity among adults with intellectual disability

Abstract: BMI appears to be a reasonable indicator of adiposity, although a BMI >or= 30 may misclassify a proportion of individuals assessed by DXA as obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 17 publications
2
38
1
Order By: Relevance
“…The prevalence of high adiposity in our study (35.8%) is also higher than a recent study in Taiwan (2016) among young female adults which is reported at 27.3% [12]. This indicates that about one third of this population which are all young adults are at high risk for non-communicable and cancer diseases [13][14].…”
Section: Discussioncontrasting
confidence: 48%
“…The prevalence of high adiposity in our study (35.8%) is also higher than a recent study in Taiwan (2016) among young female adults which is reported at 27.3% [12]. This indicates that about one third of this population which are all young adults are at high risk for non-communicable and cancer diseases [13][14].…”
Section: Discussioncontrasting
confidence: 48%
“…The results showed that four studies (67%) included participants with various levels of ID [1619] with the two remaining studies (33%) featuring participants only with Down syndrome (DS) [20, 21]. Temple et al's [17] research included individuals with DS and Duane syndrome under the generic term ID. Two additional studies included participants only with severe disabilities [16, 19] while another contained a comparison group without disabilities [21].…”
Section: Resultsmentioning
confidence: 99%
“…Four of the studies that met our inclusion criteria attempted to cross validate anthropometric measurements using a criterion measure, namely, ADP [20, 21], DXA [17], and isotope dilution [16]. The validity of skinfold thickness generalized prediction equations was tested in four studies (67%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations